Environmental education: an attempt at school- community integration - Flórez Restrepo, Gustavo Adolfo (Universidad Pedagógica y Tecnológica de Colombia, 2012)
This article springs from author’s reflection exercise on investigative and pedagogical innovation practices, bringing forth the project “Learning Community for Environmental Education and Action”. Such proposal, supported by private sector, is currently developed in twelve municipalities of the Provinces of Sugamuxi and Tundama in the Department of Boyaca. Four ideas are analytically presented and developed in this article: Environmental Education: a mean to debate on educational matters in the environmental training process, National Policy on environmental education: a guideline and foundation for the development of this kind of education in Colombia, Environmental School Projects: an exercise that enables implementation of the environmental dimension in the processes of the educational community, and, learning community: a strategy for involving the varied social actors of a given context in the understanding of the environmental dimension and in the local development. From this context, it is expected to create a reflective approach for the analysis of the existing proximity in the school-community relationship around the environmental education.